If we cannot go at the speed of light - Kim, Ch'o-yŏp, 1993- (Saga Press, an imprint of Simon & Schuster, Inc., 2026)
"In If We Cannot Go at the Speed of Light, Korean science fiction superstar Kim Cho-yeop leads us to places we never thought we'd reach, imagining worlds galaxies away and unfamiliar lifeforms with near-dizzying humanity. An elderly woman stranded in a defunct space station recounts her life story to a visitor as she waits for a vessel that may never arrive. A man comes across a company called Emotional Solids that sells emotions as material products--love as a piece of chocolate, sadness as a smooth stone, anger as a glass paperweight--and tries to understand why people would want to purchase any negative emotions. When an enigmatic artist reveals long-forgotten messages from beyond through her wildly original paintings portraying a planet from a time long before humanity formed, a team of researchers investigate if this planet truly existed and if so, how did this artist know of it? After a pregnant woman's estranged mother dies suddenly, her avatar disappears from the library of lost souls where the digital minds of the deceased are stored--and the woman is forced, for the first time, to endeavor to understand her mother. In a future utopian society where gene selection has been made uniform and all those with imperfections are cast aside, one woman seeks the truth about the history of her isolated world. And when a young woman undertakes a never-before-accomplished journey through a wormhole, she must reckon with the legacy of her aunt, who vanished mysteriously days before she was meant to begin the same pilgrimage. Traversing the bounds of imagination with an ethereal incisiveness, Kim Cho-yeop's stories dismantle the borders between normal and abnormal, material and abstract, earthly and otherworldly. With unforgettable inventiveness and pathos, If We Cannot Go at the Speed of Light heralds the arrival of an essential voice in contemporary fiction."--Amazon.